The Aftermath of Tougher Immigration Enforcement: E-Verify and Perceptions of Discrimination Among Hispanic Citizens. (August 2019) - Amuedo-Dorantes, Catalina; Pozo, Susan
Using the 2002-2012 National Latino Surveys, we assess whether enforcement of immigration law through employment verification (E-Verify) mandates has affected perceptions of discrimination among Hispanic citizens—a group that is clearly authorized to work. E-Verify could adversely affect Hispanic citizens if employers avoid hiring Hispanics for fear they could be found ineligible through this program. We find, instead, that naturalized Mexicans perceive less employment discrimination after E-Verify is mandated. Perhaps, the program provides employers with an unobtrusive mechanism to ascertain work eligibility of prospective employees, avoiding more arbitrary screening. Nonetheless, naturalized Mexicans in E-Verify states are more likely to perceive that discrimination is getting in the way of Latinos' success than their counterparts in other states. While this sentiment precedes the implementation of E-Verify and cannot be attributed to the mandates, its recognition is important because of its spillover effects on self-esteem, life dissatisfaction, and social cohesiveness.